Desarrollo Instrumental y Metodológico para Analizar y Corregir el Nistagmo Congénito - Suaste, E.; Leybón, J. (Revista Mexicana de Ingenieria Biomedica, 1998)
The biomedical instrumentation and software developed to improve visual lifestyle of patients with congenital nystagmus are described taking into account the application of vanguard methods to correct as good as possible physiological and esthetic symptoms.